Employer Organisations and Business Groups in the Czech Republic - Pinková Aneta (Sciendo, 2015)
This article is a case study focusing on employer organisations and business organisations in the Czech Republic. In legal terms, employer organisations are a specific type of interest group with special regimes of registration and record keeping. Unlike business groups, they are endowed with certain privileges and, in particular, can participate in collective bargaining. This study analyses the relations between these two types of groups. The database originates from a questionnaire-based survey undertaken in 2010 among 91 groups representing businesses and employers. The analysis focuses on the relationship between a group’s registration as an employer organisation and its orientation towards employer and business interests. It also investigates similarities between the two organisation types in terms of secondary organisation and strategies used. The analysis suggests that the differences between these two types are minimal and that the possibility of participating in collective bargaining and in tripartite counselling bodies remains the only relevant distinction. This holds true even when we take into account these groups’ self-perceived primary role, i.e. defending their members as employer or as business organisations.